The Effect of Phase Transition Temperature on Therapeutic Efficacy of Liposomal Bortezomib - Korani, Mitra; Nikoofal-Sahlabadi, Sara; Nikpoor, Amin R.; Ghaffari, Solmaz; Attar, Hossein; Mashreghi, Mohammad; Jaafari, Mahmoud R. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Aims: Here, three liposomal formulations of DPPC/DPPG/Chol/DSPE-mPEG2000 (F1), DPPC/DPPG/Chol (F2) and HSPC/DPPG/Chol/DSPE-mPEG2000 (F3) encapsulating BTZ were prepared and characterized in terms of their size, surface charge, drug loading, and release profile. Mannitol was used as a trapping agent to entrap the BTZ inside the liposomal core. The cytotoxicity and anti-tumor activity of formulations were investigated in vitro and in vivo in mice bearing tumor. Background: Bortezomib (BTZ) is an FDA approved proteasome inhibitor for the treatment of mantle cell lymphoma and multiple myeloma. The low solubility of BTZ has been responsible for the several side effects and low therapeutic efficacy of the drug. Encapsulating BTZ in a nano drug delivery system; helps overcome such issues. Among NDDSs, liposomes are promising diagnostic and therapeutic delivery vehicles in cancer treatment. Objective: Evaluating anti-tumor activity of bortezomib liposomal formulations. Methods: Data prompted us to design and develop three different liposomal formulations of BTZ based on Tm parameter, which determines liposomal stiffness. DPPC (Tm 41°C) and HSPC (Tm 55°C) lipids were chosen as variables associated with liposome rigidity. In vitro cytotoxicity assay was then carried out for the three designed liposomal formulations on C26 and B16F0, which are the colon and melanoma cancer mouse-cell lines, respectively. NIH 3T3 mouse embryonic fibroblast cell line was also used as a normal cell line. The therapeutic efficacy of these formulations was further assessed in mice tumor models. Result: MBTZ were successfully encapsulated into all the three liposomal formulations with a high entrapment efficacy of 60, 64, and 84% for F1, F2, and F3, respectively. The findings showed that liposomes mean particle diameter ranged from 103.4 to 146.8nm. In vitro cytotoxicity studies showed that liposomal-BTZ formulations had higher IC50 value in comparison to free BTZ. F2-liposomes with DPPC, having lower Tm of 41°C, showed much higher anti-tumor efficacy in mice models of C26 and B16F0 tumors compared to F3-HSPC liposomes with a Tm of 55°C. F2 formulation also enhanced mice survival compared with untreated groups, either in BALB/c or in C57BL/6 mice. Conclusion: Our findings indicated that F2-DPPC-liposomal formulations prepared with Tm close to body temperature seem to be effective in reducing the side effects and increasing the therapeutic efficacy of BTZ and merits further investigation.
Keywords: colorectal neoplasms